Rectangular learning through video, is it effective during the Covid-19 pandemic? - Lisa Fitriana; Rachmaniah Mirza Hariastuti; Novita Purnamasari Supahmi; Risa Farroh Maulida (Journal of Science and Education (JSE), 2021)
The Covid-19 pandemic is a challenge for teachers and students in the learning process, especially to implement technology-based learning. Learning mathematics with the characteristics of abstract objects makes teachers have to innovate in the knowledge transfer process. However, not all teachers can make technology-based material innovations. For this reason, it is necessary to develop learning media in the form of videos on rectangular material so that they can become additional references for teachers in learning. The videos were created with the Microsoft PowerPoint application based on the ADDIE development model. The data was collected by using questionnaires, tests, and documentation. Data analysis was carried out qualitatively based on predetermined indicators. The development results show that the video is valid according to expert judgment and the results of the student response questionnaire after the implementation process. However, in terms of material, the video has not provided effectiveness in students’ mathematical understanding.